Can Government Deliver Quality Rural Healthcare? Empirics on Malaria Prevention and Control in Nigeria - Udoudo, Mosunmola Grace Moses; Umoh, Gabriel Sunday (Asian Journal of Economic Modelling, 2015)
A large percentage of the Nigerian rural population has been plagued with several disease conditions with deleterious consequence on their health and livelihoods. One of such intractable diseases of the rural population is malaria. The governments of Nigeria and development partners have responded to the malaria scourge with various interventions. These include the Roll-Back-malaria programme, the Millennium Development Goals (Goal 6), national malaria programme, among others. Despite these efforts of the government and stakeholders in health sector, malaria prevention and control seems to be arduous especially in the rural areas, where the poor and vulnerable population live. This study attempted to address the following: (i) What quanta of resources have been invested by government on malaria control and eradication in the country? (ii) Has malaria responded to public investment in its eradication? If, not what factors specifically account for it? (iii) Are the current approaches sufficient to eradicate malaria in rural Nigeria? (iv) What can Nigeria government do to address the malaria eradication problems in the rural areas in the country? To answer these questions secondary data were used to conduct empirical analysis of public expenditure on malaria, malaria morbidity and mortality. The methods of analysis employed were: descriptive statistics, correlation and regression analysis. Result show that despite the attempts made by successive Nigerian administration to control malaria disease in the rural areas, these efforts have not yielded consistent results. Association between sources of funding and malaria were positive. The paper recommends that efforts should be directed towards vaccine production and use of predators as a means of controlling malaria, while funds released should be properly supervised.